Serum microRNA profiles among dioxin exposed veterans with monoclonal gammopathy of undetermined significance. Issue 7 (2nd April 2020) - Wang, Weixin; Shim, Youn K.; Michalek, Joel E.; Barber, Emily; Saleh, Layla M.; Choi, Byeong Yeob; Wang, Chen-Pin; Ketchum, Norma; Costello, Rene; Marti, Gerald E.; Vogt, Robert F.; Landgren, Ola; et al.
ABSTRACT: Previously an increased risk for monoclonal gammopathy of undetermined significance (MGUS), a precursor of multiple myeloma (MM), was reported among Vietnam veterans exposed to Agent Orange and its contaminant 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD). Dysregulated expression of certain microRNAs (miRNAs) was demonstrated in MGUS and MM. Given the important role of miRNAs in cellular homeostasis, the aim of this study was to determine if there was an association between serum levels of selected miRNAs and TCDD in 47 MGUS cases identified in our previous investigation using serum specimens and exposure data archived by the Air Force Health Study (AFHS). A total of 13 miRNA levels (let-7a, let-7i, miR-16, miR-20a, miR-21, miR-34a, miR-106b, miR-146a, miR-181a, miR-192, miR-205, miR-335, and miR-361) was measured in serum stored during the 2002 AFHS follow-up and the relationship to lipid-adjusted serum TCDD levels in 1987 was determined. miR-34a showed the strongest relationship with TCDD; after age-adjustment, this positive association was more pronounced. In contrast, the other 12 miRNAs displayed absolute values of age adjusted coefficient estimates below 1.16 and non-significant p -values. The observed strong positive association between high body burdens of TCDD and miR-34a, a tumor suppressor regulated by p53, in this MGUS population warrants clarification of the TCDD-miR-34a relationship and its role in the pathogenesis of MGUS and risk for MM.